Tracing Land-Based Microplastic Sources in Coastal Waters of Zhanjiang Bay, China: Spatiotemporal Pattern, Composition, and Flux - Wang, Shujia; Jian, Qiying; Zhang, Peng; Zhang, Jibiao; Zhao, Lirong; Liu, Dan; Kang, Xinhuang (Frontiers in Marine Science, 2022)
Estuaries and sewage outlets are key pathways for the transport of microplastics (MPs) from land to coastal waters. In this study, the spatiotemporal pattern, composition, and flux of MPs transported from land to Zhanjiang Bay (ZJB) in the South China Sea were investigated. The results showed that the overall mean MP abundance (± standard deviation) was 17.99 ± 9.72 items/L, with the highest in the normal season, followed by the dry and wet seasons. Fibers were the most dominant shape in these samples, blue was the most common color, and most MPs ranged between 100 and 330 μm. The MP diversity was higher in the wet and normal seasons than in the dry season. The highest seasonal flux of MPs was observed during the wet season, accounting for 79.68%, with the largest contribution from the Suixi River. There was a significant positive relationship between the annual MP flux and river discharge (R² = 0.95, p< 0.001). Hydrological processes, human behavior, and weather conditions were key factors that contributed toward the spatiotemporal variation of MPs. Overall, the aim of this study was to provide baseline information on MP pollution in ZJB to help formulate control strategies for improving regional water quality and mitigating its pollution. In the future, this study can be used to assess the role of river basins and sewage outlets in transporting MPs to the estuaries and ocean.